Analysis of the Effect of Core Stability on the Risk of Lower Extremity Injuries in Futsal Players: A Literature Review - Fachrun Nisa Sofiyah Khasanah; Itsna Rosyada (CV. SAMODRA INSAN PENA, 2026)
Futsal Futsal is a high-intensity sport characterized by rapid acceleration, deceleration, sudden changes of direction, jumping, and repetitive physical contact. These demanding movement patterns place considerable mechanical stress on the musculoskeletal system, particularly the lower extremities, making futsal players highly susceptible to injuries such as ankle sprains, knee injuries, hamstring strains, and anterior cruciate ligament (ACL) tears. Among the intrinsic factors associated with injury prevention, core stability has emerged as a critical component in maintaining spinal stability, pelvic control, and efficient body movement coordination during dynamic activities. This literature review aims to analyze the effect of core stability on the risk of lower extremity injuries in futsal players. The study employed a literature review approach by examining national and international scientific articles published between 2015 and 2026, retrieved from databases including Google Scholar, PubMed, and Scopus. The findings indicate that poor core stability is associated with impaired dynamic balance, decreased neuromuscular control, increased knee valgus, and ankle instability, all of which contribute to a greater risk of lower extremity injuries. Conversely, improved core stability has been shown to enhance movement biomechanics, optimize force distribution, and improve movement efficiency during sports performance. Therefore, core stability training should be integrated into futsal training and injury prevention programs to enhance athletic performance while reducing the incidence of lower extremity injuries futsal.